Work satisfaction and burnout risk of gastroenterologists in Germany: results of a nationwide survey - Adarkwah, Charles Christian; Labenz, Joachim; Birkner, Berndt; Beilenhoff, UIrike; Hirsch, Oliver (Zeitschrift für Gastroenterologie, 2020)
Background More and more gastroenterologists are not satisfied with their working conditions and run the risk of developing burnout symptoms. Little is known about the job satisfaction and burnout risk among physicians working in endoscopy units in Germany. This study examines the risk of burnout and job satisfaction among gastroenterologists in Germany.Methods An electronic survey was distributed to gastroenterologists organized mainly in the Federal Organization of Gastroenterology in Germany (BVGD, Berufsverband Gastroenterologie Deutschland e. V.). In addition to general demographic variables, job satisfaction was determined using the Work Satisfaction Questionnaires (WSQ), and burnout risk was determined using the Maslach Burnout Inventory (MBI).Results A representative sample of gastroenterologists organized in the BVGD (Berufsverband Gastroenterologie Deutschland e. V.) took part in the study (n = 683, 22 %). Above all, we could demonstrate relevant differences with regard to burnout risk and job satisfaction depending on the place of work, clinic structure, position in the clinic, and age. Younger physicians had significantly higher depersonalization (p < 0.001) and exhaustion scores (p < 0.001) with almost medium and small effect sizes (δt = 0.45 and −0.31). The higher the position in the clinic, the higher the accomplishment scores (medium effect size 0.27). Older physicians were especially more satisfied in the areas of patient care (p < 0.001, medium effect size δt = −0.53). Employed doctors show a higher level of satisfaction in terms of “burden” compared to practice owners (p < 0.001, δt = −0.69). Compared to norms used in the EGPRN study which were adapted to physicians, almost one-third of our sample had high depersonalization scores, about 17 % had high exhaustion scores, and about half had low personal accomplishment scores showing a higher general burden among German gastroenterologists.Conclusion Decreased work satisfaction and risk of burnout are important issues among German gastroenterologists. Specific actions should address this problem in order to avoid negative consequences, respectively.
Keywords: work satisfaction; burnout risk; Maslach Burnout Inventory (MBI); gastroenterologists; endoscopy